Pola Asuh Orang Tua dalam Menanamkan Nilai-Nilai Budaya Lokal Suku Sasak Untuk Meningkatkan Kemampuan Literasi Siswa - Muspita, Zalia; Aldawia, Zaitun; Aziz, Abdul; Zohrani, Zohrani (Mataram University, 2025)
This study aims to analyze parental parenting patterns in instilling local cultural values of the Sasak Tribe to improve literacy skills of fifth-grade students at MI NWDI Pringgasela. This study used a qualitative approach with descriptive methods. The research was conducted at MI NWDI Pringgasela. The research subjects were fifth-grade teachers, fifth-grade students, and parents. The data sources used were primary and secondary data. Data collection techniques were conducted through observation, interviews, and documentation. The results show that parenting patterns are highly influential in instilling local cultural values to improve children’s literacy skills. Appropriate parenting patterns can have a positive impact on children’s growth and development, both in terms of social interaction and learning. However, this is different for children who live with their grandparents, which shows significant differences in the child’s growth and development. This contrast is stark when children learn in class. One child’s literacy skills are still low because he doesn’t know the alphabet, which prevents him from reading and writing. Upon further investigation, it turns out he comes from a broken home, where a lack of attention hinders his learning. In this regard, the role of parents is crucial. Providing books, telling stories to children, and allowing them to participate in culturally themed activities can improve children's literacy skills.